Mortality in women of reproductive age in rural South Africa - Nabukalu, Doreen (My University, 2012)
Objective: To determine the causes of death and associated risk factors in women of reproductive age in rural South Africa. . Methods: The study population comprised all female members aged 15-49 years of 11 000 households of a rural South African Health and Demographic Surveillance Site from 2000-2009. Deaths and person-years of observation (pyo) were determined for individuals between 01 January 2000 and 31 December 2009. Cause of death was ascertained by verbal autopsy interviews, based on ICD-10 coding; cause of death were broadly categorized as AIDS/TB causes, Non-communicable causes, Communicable/maternal/perinatal/nutrition causes, Injuries and another category of undetermined (unknown) causes of death. Overall and cause specific mortality rates (MR) with 95% confidence intervals (CI) were calculated. Cox proportional hazard regression (HR, 95% CI) was used to determine risk factors associated with overall and cause-specific mortality. Results: 42703 eligible women were included; 3098 deaths were reported for 212607 person-years (pyo) of observation. Overall MR was 14.57 deaths/1000 pyo (CI;14.07-15.09), increasing from 2000-2003 (2003: MR;18.15, CI;16.41-20.08) and subsequently decreasing (2009: MR; 9.59, CI;8.43-10.91) after introduction of antiretroviral treatment (ART) for HIV in public health system facilities in South Africa in 2004. Mortality was highest for AIDS/TB (MR;10.66, CI;10.23-11.11) and the cause of death for 73.1% of all recorded deaths. Maternal mortality was 0.07 (CI; 0.04-0.11). Women aged 30-34 years had the highest MR due to AIDS/TB (MR; 20.34/1000 pyo), women aged 45-49 years due to other causes (MR; 4.29/ 1000 pyo). v In multivariable analyses, external migration status was associated with increased hazards of all cause mortality (HR; 1.87, CI; 1.56-2.26) and other causes of mortality (HR; 1.782, CI; 1.24-2.57). Self reported poor health was significantly associated with increased hazards of all cause mortality (HR; 11.052, CI; 4.24-28.82) but not with mortality due to other causes. Positive HIV status was associated with increased hazards of all cause mortality (HR; 8.53, CI; 6.81-10.67) and other causes of mortality (HR; 2.84, CI; 1.97- 4.09). Conclusion. AIDS was the main cause of death in the current study, with mortality rates declining since introduction of ART for HIV in public health facilities in the surveillance area in 2004. Further ART roll-out, increased community awareness and sensitisation messages are still needed to reduce the spread of HIV and other sexually transmitted diseases.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the award of the Masters in Science in Epidemiology in the field of Population-based Field Epidemiology April 2012
Keywords: Mortality -- statistics; Maternal Mortality -- South Africa